In‐depth comparison of N‐glycosylation of human plasma‐derived factor VIII and different recombinant products: from structure to clinical implications. (27th July 2018) - Canis, K.; Anzengruber, J.; Garenaux, E.; Feichtinger, M.; Benamara, K.; Scheiflinger, F.; Savoy, L.‐A.; Reipert, B. M.; Malisauskas, M.
Abstract : Essentials Glycosylation heterogeneity of recombinant proteins affects pharmacokinetics and immunogenicity. N ‐glycomics/glycoproteomics of plasma‐derived Factor VIII and 6 recombinant FVIIIs were compared. Depending on cell line, significant differences to plasma‐derived FVIII were observed. Recombinant FVIIIs expressed distinct and immunologically relevant epitopes. Summary: Background/Objective: Human factor VIII (FVIII) is a plasma glycoprotein, defects of which result in hemophilia A. Current substitution therapy uses FVIII products purified from human plasma or from various cell lines (recombinant FVIII) with different levels of B‐domain deletion. Glycosylation is a post‐translational protein modification in FVIII that has a substantial influence on its physical, functional and antigenic properties. Variation in glycosylation is likely to be the reason that FVIII products differ in their pharmacokinetics, pharmacodynamics and immunogenicity. However, the literature on FVIII glycosylation is inconsistent, preventing assembly into a coherent model. Seeking to better understand the glycosylation mechanisms underlying FVIII biology, we studied the N ‐glycosylation of human plasma‐derived (pd)FVIII and six rFVIII products expressed in CHO, BHK or HEK cell lines. Methods: FVIII samples were subjected to head‐to‐head detailed glycomic and glycoproteomic characterization using a combination of MALDI‐MS and MS/MS, GC‐MS and UPLC‐UV‐MS E technologies. Results/Conclusion: The results of our study detail the N ‐glycan repertoire of pdFVIII to an unprecedented level, and for the first time, provide evidence of N ‐glycolylneuraminic acid (NeuGc) found on pdFVIII. Although site‐specific glycosylation of rFVIII proved consistent with pdFVIII regardless of the expression system, the entire N ‐glycan content of each sample appeared significantly different. Although the proportion of biologically important epitopes common to all samples (i.e. sialylation and high‐mannose) varied between samples, some recombinant products expressed distinct and immunologically relevant epitopes, such as LacdiNAc (LDN), fucosylated LacdiNAc (FucLDN), NeuGc, Lewis X/Y and Galα1, 3 Gal epitopes. rFVIII expressed in HEK cells showed the greatest glycomic differences to human pdFVIII.